2015
DOI: 10.1007/s12046-014-0319-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical optimization of a transcritical CO 2 /propylene cascaded refrigeration-heat pump system with economizer in HT cycle

Abstract: Use of organic refrigerants such as Hydrochlorofluorocarbons and Chlorofluorocarbons have been criticized for their adverse impact on the Earth's protective ozone layer and for their significant global warming potential (GWP). CO 2 has been receiving great concern as an alternative refrigerant. Cascade refrigeration systems employing CO 2 are used for low temperature applications. Being a low critical temperature fluid CO 2 transcritical cascade systems offer low COP for a given application. Parallel compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The fluorescence light spectral profile as a function of the activator concentration was examined and the results indicated that the chromaticity coordinates of the overall emission light changed resulting in different colors of the overall emission light, for different concentrations as can be observed. The PL spectra is quite similar from our previous study on Eu 3þ doped Y 2 O 3 and SrY 2 O 4 phosphor and the prepared phosphor shows good results as compared to our previous work [26,29,33]. 3.6.…”
Section: Transitionsupporting
confidence: 84%
“…The fluorescence light spectral profile as a function of the activator concentration was examined and the results indicated that the chromaticity coordinates of the overall emission light changed resulting in different colors of the overall emission light, for different concentrations as can be observed. The PL spectra is quite similar from our previous study on Eu 3þ doped Y 2 O 3 and SrY 2 O 4 phosphor and the prepared phosphor shows good results as compared to our previous work [26,29,33]. 3.6.…”
Section: Transitionsupporting
confidence: 84%
“…The effectiveness of the subcooler 30 . can be defined as the ratio of temperature difference between two streams of fluid in the subcooler: α=T8T14T8T16. …”
Section: Model Description and Simulationmentioning
confidence: 99%
“…For design parameters, thermal performance calculated for different combinations of design parameters and optimum performance parameters such as COP max , T opt and mass flows of R744 and R1270 evaluated. At the another work [15] numerical optimization of a transcritical R744 /R1270 cascade refrigeration -heat pump system with economizer in HT cycle carried out. At this work by using parallel compression economization in the HT cycle as the modification to improve the COP of transcritical cascaded systems, simulation for cooling/heating applications carried out.…”
Section: Introductionmentioning
confidence: 99%